The UK's Participation in Global Value Chains and Its Implications for Post‐Brexit Trade Policy1. (18th December 2018) - IJtsma, Pieter; Levell, Peter; Los, Bart; Timmer, Marcel P.
Abstract: The aim of this paper is to provide quantitative information about the position of the UK in the network of global value chains (GVCs) and to discuss its implications for the UK's post‐Brexit trade policy. We find that the UK has become much less integrated into global production networks than other EU countries over the period 2000–14, and is almost unique among EU countries in that the domestic content of its exports increased over this period. This reflects the relatively high and growing domestic service content in UK exports. As a result of this, reducing the UK's tariffs on imported goods is unlikely to have a large direct effect on the average export competitiveness of UK firms. Potentially more significant for the UK is how future trade barriers with the EU are likely to affect its participation in cross‐country value chains that meet final demand in markets in North America and East Asia. Such indirect exports are not captured in conventional trade statistics and can only be analysed using a GVC approach. Our findings suggest that the UK will benefit only to a limited extent from bilateral trade agreements with countries outside the EU (a 'Global Britain' strategy) if it gives up its role in the supply chains that service these countries via the EU hub.